Mobility and Ideological Perspective of Asano Akira in Java During Period of Japan Occupation - Syahrur Marta Dwisusilo; Lucitra A. Yuniar (Universitas Airlangga, 2020)
The period of Japanese occupation for 3 years in Indonesia is sort when compared to the Dutch colonial period. However, at that time it was a critical time for the formation of various ideological thoughts. One of the ideologies that emerged in the Japanese colonial era was the ideology of